Cystic struma ovarii: a rare presentation of an infrequent tumor - Carvalho, Rita Barbosa de; Cintra, Maria Letícia; Matos, Patrícia Sabino de; Campos, Paulo Sérgio Bueno de (São Paulo Medical Journal, 2000)
CONTEXT: Struma ovarii, a rare neoplasm, is a monophyletic teratoma composed of thyroid tissue. It is generally considered to account for less than 5% of mature teratomas. CASE REPORT: A diagnosis of struma ovarii may be the source of many diagnostic problems. It may be cystic and microscopic examination may only reveal a few typical thyroid follicles, resulting in confusion with other cystic ovarian tumors. Extensive sampling should be undertaken and immunohistochemistry may be decisive in establishing the thyroid nature of the epithelial lining. The authors report two cases of cystic struma ovarii, and discuss diagnostic criteria and the limitations of frozen biopsies in these tumors.